The accuracy of computed tomography for clavicle non-union evaluation. (April 2021) - Nicholson, Jamie A; Fox, B; Dhir, R; Simpson, AHRW; Robinson, CM
Background: The primary aim of this study is to determine the accuracy of CT scanning when evaluating non-union of the clavicle. Methods: A retrospective review was performed of all CT scans undertaken for suspected nonunion of midshaft clavicle fractures over a 10-year period. The influence of scan timing, callus and patient characteristics was evaluated. Results: One hundred eighty-four CT scans were analysed. No patient was incorrectly diagnosed with union ( n = 85). Ninety-nine scans were reported as non-union with inadequate bridging callus, 19 of which were united at operation or on repeat CT imaging and represented delayed unions. Atrophic callus was found in 57 patients and all of which had a confirmed non-union (positive predictive value 100%). A hypertrophic callus was found in 42 patients, all of the delayed unions were found in this group (positive predictive value for non-union 55%, p < 0.001). CT compared to radiographs showed greater inter-observer agreement for union (weighted kappa 0.75 vs. 0.50 respectively). Overall, CT is 100% sensitive and 81.7% specific for non-union diagnosis. Discussion: CT has excellent accuracy to determine clavicle union but approximately one in five suspected non-unions went onto unite. Hypertrophic callus finding resulted in a delayed union in approximately half of the cases in our study.